Understanding the Spectrum of Congenital Abnormalities Impacting Female Fertility Through MRI Imaging - Zubdah Najam, Tasbiha Hasnain, Sobia Naz, Fatima Khawar, Sana Noor, Esha Habib Butt, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Congenital uterine anomalies (CUAs) are structural malformations of the female reproductive tract that arise from disrupted development, fusion, or resorption of the Müllerian ducts. Objective: To evaluate the spectrum of congenital uterine anomalies affecting female fertility and to assess the diagnostic utility of MRI in identifying and classifying these abnormalities. Methodology: This was a cross-sectional descriptive study conducted at Sir Ganga Ram Hospital Lahore during December 2022 and May 2023. A total of 110 female patients were included in the study. Non-probability consecutive sampling was used. All MRIs were performed using a 1.5 Tesla system. The imaging protocol included T1-weighted and T2-weighted sequences in axial, sagittal, and coronal planes. Special emphasis was placed on T2-weighted images for optimal delineation of uterine zonal anatomy. Results: The most common anomaly detected was septate uterus (29.1%), followed by bicornuate uterus (19.1%) and uterine agenesis/hypoplasia (16.4%). A significant association was found between septate uterus and recurrent miscarriage (p = 0.031), as well as between uterine agenesis and primary amenorrhea (p < 0.001). Renal anomalies were present in 11.8% and vaginal anomalies in 8.2% of cases. MRI allowed precise differentiation between surgically correctable and non-correctable anomalies and revealed associated extra-genital findings in multiple cases. Conclusion: MRI is a highly accurate, non-invasive tool for the evaluation of congenital uterine anomalies. It offers superior anatomical detail, enables appropriate classification, and guides effective clinical and surgical management. Early identification of these anomalies through MRI can significantly improve reproductive outcomes and prevent unnecessary interventions. Keywords: Congenital uterine anomalies, Müllerian duct anomalies, infertility, MRI, septate uterus, bicornuate uterus.